Pengaruh Motivasi, Persepsi, dan Sikap terhadap Keputusan Pembelian Body Lotion Vaseline pada Mahasiswa UIN Sultan Syarif Kasim Riau - Wirza Kurnia Ananda; Ainun Mardiah (Al-Manar Journal of Accountancy and Business Studies, 2026)
This study aims to analyze the influence of motivation, perception, and attitude on the purchasing decisions of Vaseline Body Lotion among students of UIN Sultan Syarif Kasim Riau. The research employed a quantitative approach using a survey method through the distribution of questionnaires to 96 respondents who had used Vaseline Body Lotion, with purposive sampling as the sampling technique. The data analysis technique used was multiple linear regression with the assistance of the SPSS program, including validity tests, reliability tests, classical assumption tests, t-tests (partial), F-tests (simultaneous), and coefficient of determination tests (R²). The results of the study indicate that partially, motivation has a positive and significant effect on purchasing decisions. Meanwhile, perception does not have a significant effect on purchasing decisions, while attitude has a positive and significant effect on purchasing decisions. Simultaneously, motivation, perception, and attitude significantly influence purchasing decisions, with an F-value of 29.631 and a significance level of 0.000. The coefficient of determination (R²) value of 0.500 indicates that the three independent variables are able to explain 50% of the variation in purchasing decisions, while the remaining 50% is influenced by other variables outside this study. These findings confirm that consumer motivation and attitude play an important role in increasing purchasing decisions for Vaseline Body Lotion among students of UIN Sultan Syarif Kasim Riau